Monopoly behaviour of the DeBeers Diamond Company - Dilafruz Kuchkorova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Monopoly is the dominating one firm in the market, there is no competitors or no other substitute firms in the market. Monopoly has an ability to set price on his own product. Many researches have been analysed the efficiency of monopoly and its effects to consumer behaviour. The inefficiency of Monopoly is proved by price is above the marginal cost and it causes the shortage of product in the market. Thus, monopolist produces and sells the limited quantity of product and it is below the rank the social efficient level. This coursework has been conducted on the monopoly behaviour of DeBeers Diamond Company. In the Introduction section numerous papers on the efficiency of a monopolistic market have been revived and analysed. In the body part natural barriers to entry, unfair competition of computer software markets, monopoly pricing and social cost of diamond market have been discussed, and in final part how social cost occurs the government intervention to the market have been demonstrated.